Evaluation of platelet response to different clopidogrel dosing regimens in patients with acute coronary syndrome in clinical practice. (11th March 2014) - Fefer, Paul; Beigel, Roy; Rosenberg, Nurit; Shechter, Michael; Gannot, Sharon; Varon, David; Savion, Naphthali; Hod, Hanoch; Matetzky, Shlomi
Abstract: High-post clopidogrel platelet reactivity in acute coronary syndrome (ACS) patients is associated with adverse outcomes and may be related to clopidogrel dosing. Clinical studies evaluating different clopidogrel doses have resulted in conflicting conclusions. Clopidogrel dosing regimens have evolved over time, enabling us to evaluate platelet reactivity in real-life ACS patients undergoing percutaneous coronary intervention and treated with three different clopidogrel doses. Platelet reactivity was assessed with light transmitted aggregometry on the third day post clopidogrel loading in 404 consecutive ACS patients. Of them, 198 were treated with a standard regimen (300 mg loading, 75 mg/day maintenance dose), 95 with a high loading regimen (600 mg loading, 75 mg/day maintenance dose) and 111 with a high loading/high maintenance regimen (600 mg loading, 150 mg/day maintenance). Compared with the standard regimen, the high loading regimen resulted in significantly lower mean platelet reactivity to adenosine diphosphate (ADP) with a lower proportion of patients exhibiting clopidogrel non-responsiveness (11% vs. 28%, p = 0.004). Compared with the high loading regimen, the high loading/high maintenance regimen resulted in significantly lower mean platelet reactivity to ADP, but without a further drop in the number of non-responders (8.1% vs. 11%, p = 0.16). In conclusion, greater overall inhibition can be achieved with higher loading and maintenance doses in ACS patients. However, despite high clopidogrel doses, a sizable proportion of patients remained "resistant" to the effects of clopidogrel.